Isolation, characterization and chromatography based purification of antibacterial compound isolated from rare endophytic actinomycetes Micrococcus yunnanensis - Ravi Ranjan; Vasantba Jadeja (Elsevier, 2017)
Endophytic actinomycetes are considered as one of the relatively unexplored potential sources in search of antibiotic producer against antibiotic resistant pathogens. A potent strain isolated from Catharanthus roseus that displays antibacterial potential against antibiotic resistant human pathogen Staphylococcus aureus was characterized and designated as Micrococcus yunnanensis strain rsk5. Rsk5 is capable of producing optimum antibacterial metabolites on starch casein medium at 30 °C, pH 5 and 2% NaCl condition. The crude antibacterial agent was extracted from fermentation broth by ethyl acetate and separated by TLC using chloroform-methanol (24:1, v/v) solvent system with Rf value of 0.26. It was partially purified by flash chromatography, followed by HPLC and analyzed by ultraviolet visible spectrophotometer to get absorption maxima at 208.4 nm. The ESI-MS spectra showed molecular ion peaks at m/z 472.4 [M-H], which does not match with any known antibacterial compound.